2010
DOI: 10.1007/s00383-010-2618-1
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of ibuprofen against caustic esophageal burn injury in rats

Abstract: Based on these results, we concluded that the treatment with ibuprofen in acute phase esophageal burn injury has beneficial effects on healing of esophagus and may decrease the stricture formation. For these reasons, ibuprofen may effectively be used in the acute phase treatment of caustic esophagus injury and after esophageal dilatation procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…The latter suggests that the anti-fibrotic and anti-apoptotic effects of OLM administration in esophageal caustic burn observed in our study could be also attributed to the suppression of oxidative stress by AT1R antagonism. This hypothesis is in agreement with the results of previous studies which demonstrated partially successful treatment of caustic esophageal burns by increasing the antioxidant capacity of the tissue [25][26][27][28][29][30][31][32][33][34][35]. The present study provides new evidence that the renin-angiotensin system can be a promising target for the treatment of esophageal burns caused by corrosive agents.…”
Section: Discussionsupporting
confidence: 93%
“…The latter suggests that the anti-fibrotic and anti-apoptotic effects of OLM administration in esophageal caustic burn observed in our study could be also attributed to the suppression of oxidative stress by AT1R antagonism. This hypothesis is in agreement with the results of previous studies which demonstrated partially successful treatment of caustic esophageal burns by increasing the antioxidant capacity of the tissue [25][26][27][28][29][30][31][32][33][34][35]. The present study provides new evidence that the renin-angiotensin system can be a promising target for the treatment of esophageal burns caused by corrosive agents.…”
Section: Discussionsupporting
confidence: 93%
“…The ideal application is to give slow and small doses in the form of instillation (Demirbilek et al 1994). In different studies, NaOH solution (10–40%; Herek et al, 2010) was applied in the lumen between 60 s (Senturk et al, 2010) and 3 min intervals (Duman et al, 2011). In our study, NaOH solution was applied at a strength of 37.5% over a period of 60 s, and then the solution was aspirated.…”
Section: Discussionmentioning
confidence: 99%
“…Although several treatment protocols have been devised and used to accomplish anti-inflammatory and anti-fibrogenic actions, the benefit and standardization of these treatment methods are still controversial [3]. Nowadays, the effects of many therapeutic agents in preventing esophageal stricture formation continue to be investigated in experimental caustic esophageal burn injury models [4,5].…”
Section: Introductionmentioning
confidence: 99%